2023
DOI: 10.3138/jammi-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection outcomes associated with the Delta variant: A prospective cohort study

Abstract: BACKGROUND: It is well established that fully vaccinated (≥2 doses) individuals may develop COVID-19. However, little is known about the specific prevalence of post-COVID-19 conditions associated with the Delta variant or the effect of vaccination on post-acute outcomes of COVID-19. In addition, how Delta variant infection severity compares in fully vaccinated individuals versus in those unvaccinated is unknown. METHODS: This prospective single-centre observational cohort study assessed adults with SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
4
2
0
Order By: Relevance
“…The prevalence of PCC in our study population was 48%. That proportion is congruent with other studies [ 10 , 21 , 22 , 23 , 24 ]. Describing functional impacts in patients with PCC is essential since it could affect the burden of their condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of PCC in our study population was 48%. That proportion is congruent with other studies [ 10 , 21 , 22 , 23 , 24 ]. Describing functional impacts in patients with PCC is essential since it could affect the burden of their condition.…”
Section: Discussionsupporting
confidence: 92%
“…We also explored factors that can predict the occurrence of PCC. Consistent with other studies, we found that the numbers of symptoms at onset is the main predictor of PCC [ 22 , 23 ]. We also observed that participants with PCC without fatigue showed a higher prevalence of comorbidities and higher number of symptoms at onset.…”
Section: Discussionsupporting
confidence: 92%
“…In all PCC and No-PCC cases, the acute of disease was mild and none could be categorized as moderate or severe according to WHO criteria. However, the number of the symptoms reported at the acute disease was significantly higher in PCC groups than in No-PCC groups in both males (6 versus 4) and females (7 versus 5) (Mann Whitney test, males-No-PCC versus PCC, p=0.0035; females-No-PCC versus PCC, p<0.0001), in agreement with previous reports (Gallant et al, 2022a;Gallant et al, 2022b;Perlis et al, 2022;Sudre et al, 2021). Notably, in female PCC cases the number of comorbidities positively correlated with age, BMI and the number of PCC symptoms reported at 1-, 3and 6-months post-infection (Supplementary Figure S1, supplementary Table S4).…”
Section: Increased Prevalence Of Pcc Symptoms and Their Positive Corr...supporting
confidence: 91%
“…PCC encompasses a spectrum of clinical illnesses affecting multiple organs that persist for more than 3 months after the resolution of the initial infection (Nalbandian et al, 2021;Sudre et al, 2021;Sykes et al, 2021). It is estimated that 75-90% of SARS-CoV-2 infected individuals develop a mild COVID-19 disease and 5-50% percent of them develop symptoms of PCC for reasons that still remain unclear (Gallant et al, 2022b;Global Burden of Disease Long et al, 2022). Pre-existing co-morbidities, high level of SARS-CoV-2 viremia, presence of antibodies to type-I IFNs, reactivation of EBV or CMV-specific T cells during acute infection and anti-SARS-CoV-2 antibody signatures are some of the factors suggested to predict PCC in individuals with moderate to severe COVID-19 (Cervia et al, 2022;Peluso and Deeks, 2022;Su et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…PCC encompasses a spectrum of clinical illnesses affecting multiple organs that persist for more than 3 months after the resolution of the initial infection (5)(6)(7). It is estimated that 75-90% of SARS-CoV-2 infected individuals develop a mild COVID-19 disease and 5-50% percent of them develop symptoms of PCC for reasons that still remain unclear (8,9). Pre-existing co-morbidities, high level of SARS-CoV-2 viremia, presence of antibodies to type-I IFNs, reactivation of EBV or CMVspecific T cells during acute infection and anti-SARS-CoV-2 antibody signatures are some of the factors suggested to predict PCC in individuals with moderate to severe COVID-19 (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%